2018
DOI: 10.1038/s41598-018-28300-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between interleukin (IL)-6 and brain morphology in drug-naïve, first-episode major depressive disorder using surface-based morphometry

Abstract: There is a growing body of evidence to support the involvement of proinflammatory cytokines in the pathophysiology of depression; however, no previous studies have examined the relationship between cytokines and the brain morphology of patients with major depressive disorder (MDD). We therefore evaluated the relationship between serum cytokine levels and cortical thinning during the first depressive episode in drug-naïve patients with MDD. We measured the serum cytokine levels (IL-1β, IL-6, IFN-γ, and TNFα), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…49 Moreover, work by Kakeda and colleagues (2018) demonstrated a significant inverse relationship between IL-6 levels and surface-based cortical thickness and hippocampal subfields in medication-free, first-episode MDD patients. 50 This accords with the current observation of increased brain-PAD in medication-free and first-episode patients, compared to controls, perhaps suggesting that neuroimmune mechanisms may be chief candidates involved in the brain morphology alterations, also in the early stage of illness. Further, the age-related structural alterations in MDD may also be explained by shared underlying (epi)genetic mechanisms involved in brain development and plasticity (thereby influencing brain structure) and psychiatric illness.…”
Section: Discussionsupporting
confidence: 86%
“…49 Moreover, work by Kakeda and colleagues (2018) demonstrated a significant inverse relationship between IL-6 levels and surface-based cortical thickness and hippocampal subfields in medication-free, first-episode MDD patients. 50 This accords with the current observation of increased brain-PAD in medication-free and first-episode patients, compared to controls, perhaps suggesting that neuroimmune mechanisms may be chief candidates involved in the brain morphology alterations, also in the early stage of illness. Further, the age-related structural alterations in MDD may also be explained by shared underlying (epi)genetic mechanisms involved in brain development and plasticity (thereby influencing brain structure) and psychiatric illness.…”
Section: Discussionsupporting
confidence: 86%
“…Some have reported increased cortical thickness in patients with MDD compared with healthy controls (HCs) in the orbitofrontal cortex (OFC) [7,8], rostral middle frontal gyrus [7], superior frontal gyrus [8], parietal cortex [9], temporal cortex [10,11], cingulate cortex [7,9], occipital cortex [12], and insula [11]. Other studies have reported decreased cortical thickness in MDD in the middle frontal gyrus as well as OFC [13,14], parietal cortex [15], temporal cortex [9,16], occipital cortex [13], insula [11], anterior cingulate cortex (ACC), and parahippocampus [17]; some studies have reported no cortical thickness differences in these regions [18,19]. These discrepancies may be explained by study differences in sample size, patient characteristics, clinical symptom severity, medication status, and image acquisition and processing protocols.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the prefrontal cortex thickness was significantly reduced in MDD patients, and showed a significant inverse correlation with the serum IL-6 level. High levels of serum IL-6 were associated with reduced left subiculum and right CA1, CA3, CA4, GC-DG, subiculum and whole hippocampus volumes in MDD patients [54].…”
Section: Il-6 and Mdd Featuresmentioning
confidence: 86%
“…IL-6 levels may be associated with the phenotypes of MDD. An interesting research done by Kakeda et al investigated the relationship between IL-6 levels and brain morphology in first-episode drug-naïve MDD patients [54]. They found that the prefrontal cortex thickness was significantly reduced in MDD patients, and showed a significant inverse correlation with the serum IL-6 level.…”
Section: Il-6 and Mdd Featuresmentioning
confidence: 99%